New records of sea anemones (Cnidaria: Anthozoa) from Costa Rica - Acuña, Fabián H. (2013)
Despite being important components in coastal marine systems, sea anemones have been poorly studied on both coasts of Costa Rica. In this paper new records of sea anemones are mentioned for the Caribbean and Pacific coasts of Costa Rica and the Isla del Coco National Park. Additionally, the presence of other species previously recorded in Costa Rica based on single observations or photos, is reconfirmed. An updated inventory of these cnidarians is provided, and with the corallimorpharians, comprises of 16 species (10 in the Caribbean and 6 in the Pacific and Coco Island). A comparison with the sea anemone fauna of Panama is added.